Assessing Dietary Exposure of Potentially Toxic Elements via Fish Consumption - Pipoyan, D. A.; Chirkova, V. I.; Beglaryan, M. R.; Stepanyan, S. A. (ՀԱԱՀ հիմնադրամ)
This study aims to assess the consumer health risk caused by metals in fish produced in Armenia. The collected fish samples were analyzed for copper, lead, molybdenum, and arsenic via the atomic-absorption spectrometry (AAS) method. Clusters of consumers were created after conducting public surveys and analyzing data. Risk assessment was done based on the Margin of Exposure (MOE). The results indicated that the consumer health risk is within allowable limits. Moreover, the study identified factors that influence the toxicity level of the product, pointing to a necessity for a more comprehensive approach to risk assessment.
Keywords: Food Science and Technology